Poly(2‐Hydroxyethyl Methacrylate) Hydrogel‐Based Microneedles for Metformin Release - Sharma, Manoj B.; Kap, Özlem; Abdelmohsen, Hend A. M.; Ashton, Mark D.; Harper, Garry R.; Firlak, Melike; Aaltonen, Jasmine E.; Bolland, Kerry A.; Bragg, Ryan; Deeley, Sarah; Francis, Ella; Kazi, Nahin; et al. (Global challenges, 2023)
The release of metformin, a drug used in the treatment of cancer and diabetes, from poly(2‐hydroxyethyl methacrylate), pHEMA, hydrogel‐based microneedle patches is demonstrated in vitro. Tuning the composition of the pHEMA hydrogels enables preparation of robust microneedle patches with mechanical properties such that they would penetrate skin (insertion force of a single microneedle to be ≈40 N). Swelling experiments conducted at 20, 35, and 60 °C show temperature‐dependent degrees of swelling and diffusion kinetics. Drug release from the pHEMA hydrogel‐based microneedles is fitted to various models (e.g., zero order, first order, second order). Such pHEMA microneedles have potential application for transdermal delivery of metformin for the treatment of aging, cancer, diabetes, etc. Microneedle arrays are minimally invasive drug delivery devices that can be designed to deliver a variety of payloads the skin and other targets. Here, their application for the release of metformin in vitro is reported, which may combat aging, cancer, diabetes, etc.